Pembaruan Hukum Islam dalam Kompilasi Hukum Islam - Gunawan, Edi (State Institute of Islamic Studies (IAIN) Palu, 2015)
This paper discusses the reform of Islamic law in the Islamic Law Compilation. The main sources of Islamic law are the Quran and Sunnah shall be applied to the human race. Therefore, Islamic law must be able to respond to development and change that occur in peoples lives. Reform of Islamic law as the search for relevance to the development of contemporary Islamic law is not a stand-alone effort, but is influenced by internal factors and external factors. One Islamic law in Indonesia in the form of the regulation that has become positive law is Islamic Law Compilation. Several articles in the Islamic Law Compilation is a form of Islamic law reform. Whether it relates to marriage or about donation such grants could be a legacy. There are many other clauses which are part of the reform of Islamic law in the Islamic law compilation.